Analysis of Current Tools and Methods for Optimizing The Educa-Tional Process in The Context of Digital and Technological Development - Kochkonbaeva, Sonaim; Brovina, Fisnik; Borboeva, Gulnisa; Egemnazarova, Aichurok; Daniiarova, Saikal (International Journal of Basic and Applied Sciences, 2025)
The impact of technologies on educational programs and the role of new technologies in adapting educational models to the challenges of globalization and innovation are considered. Special attention is paid to the analysis of practices used in Albania and Kyrgyzstan. Key areas of digitalization of education are examined, including the introduction of cloud technologies that ensure the accessibility of educational materials from anywhere, the use of artificial intelligence for adaptive learning, which allows personalizing the educational process, and the use of virtual and augmented reality technologies for creating an interactive learning environment. The possibilities of mobile training to increase the flexibility of the educational process and use the analysis of large data for monitoring and improving educational systems are also considered. The paper focuses on a comparative analysis of the digitalization of education in Albania and Kyrgyzstan, identifying both common problems related to access to technologies and digital resources, and unique features, including differences in the level of infrastructure development, financial support, and training of teaching staff. The results of the study show that despite substantial differences in the level of digitalization, both countries are actively striving to improve the availability and quality of education through digital technologies. However, implementation processes face problems such as limited financial resources, insufficient teacher training, and unequal access to technology, especially in remote areas. Recommendations are proposed for improving the digitalization of educational processes in these countries, considering national characteristics and needs.